Loan Phonology - Calabrese, Andrea; Wetzels, Leo (John Benjamins Publishing Company, 2009)
For many different reasons, speakers borrow words from other languages to fill gaps in their own lexical inventory. The past ten years have been characterized by a great interest among phonologists in the issue of how the nativization of loanwords occurs. The general feeling is that loanword nativization provides a direct window for observing how acoustic cues are categorized in terms of the distinctive features relevant to the L1 phonological system as well as for studying L1 phonological processes in action and thus to the true synchronic phonology of L1. The collection of essays presented in this volume provides an overview of the complex issues phonologists face when investigating this phenomenon and, more generally, the ways in which unfamiliar sounds and sound sequences are adapted to converge with the native language's sound pattern. This book is of interest to theoretical phonologists as well as to linguists interested in language contact phenomena.